Civil Liability for Clients Who Suffer Losses in Using the Services of an Attorney Using Artificial Intelligence - Sholikhatus Hidayati; Uswatun Hasanah (Journal of Law, Politic and Humanities, 2024)
Artificial Intelligence has become an inseparable part of everyday life. Artificial Intelligence has been designed to help humans in various ways. included in the legal profession of an advocate to serve clients. Artificial Intelligence can be a tool in serving clients by not eliminating or changing the function and position of the advocate profession by considering, examining the data or documents provided by Artificial Intelligence. Advocates can use Artificial Intelligence to automate data document processing. This includes classifying documents, highlighting important issues, and extracting relevant information from them. By using Artificial Intelligence document processing can be done quickly and efficiently, thereby saving time and costs. With various types of Artificial Intelligence, of course there are errors and losses for users that cannot be avoided. In the use of Artificial Intelligence, it is found that the injured party is the client. With the discrepancy in the data results provided by Artificial Intelligence, this causes the client to be harmed because there is a discrepancy in the data and facts which makes the client feel that there is an error that the data processing robot should have carried out the data analysis to produce result B even though the data.